Strain localization during discontinuous plastic flow at extremely low temperatures. (15th October 2016) - Tabin, J.; Skoczen, B.; Bielski, J.
Highlights: The paper deals with an extended, physically based, multiaxial constitutive model of discontinuous plastic flow, including new feature of strain localization at near 0 K temperatures in polycrystalline materials. Another new feature defines the drop of stress being entirely determined by dislocations density before and after the serration. Regular way of nucleation and free unconstrained glide of slip bands is observed within the sample, in the absence of phase transformation. Contrary to former views, strong coupling of discontinuous plastic flow with fcc-bcc phase transformation in metastable materials is observed. Abstract: The phenomenon of strain localization in the course of discontinuous plastic flow (DPF) at extremely low temperatures is investigated. DPF is observed mainly in fcc metals and alloys strained in cryogenic conditions, practically down to absolute zero. These materials undergo at low temperatures a process similar to dynamic strain ageing, manifested by the so called serrated yielding (DPF). DPF is attributed to the mechanism of local catastrophic failure of lattice barriers (including Lomer–Cottrell locks), under the stress fields related to the accumulating edge dislocations. Failure of LC locks leads to massive motion of released dislocations, accompanied by step-wise increase of the strain rate (macroscopic slip) and drastic drop of stress. Recent experiments indicate strong strain localization in the form of shear bands propagating along the sample. The plastic power dissipated in the shear band is partially converted to heat, which results in a local drastic increase of temperature promoted by the so-called thermodynamic instability (nearly adiabatic process). The Dirac-like temperature function is measured by two thermometers located in the gage length of the sample. Spatio-temporal correlation indicates smooth shear band propagation, as long as the process of phase transformation remains on hold. A physically based multiaxial constitutive model presented in the paper describes both DPF and strain localization, accompanied by temperature distribution represented by Green-like solution of heat diffusion equation. The model accounts for the thermodynamic background, including phonon mechanism of heat transport, accompanied by specific heat vanishing with the temperature approaching absolute zero. Experimental identification of parameters of the constitutive model is carried out. A projection of the model to the range where the phase transformation takes place is discussed.